First record of Clastoptera sp. (Hemiptera: Cercopidae) on coffee plants in Brazil - Sánchez Soto, Saúl (ENTOMOTROPICA, 2007)
Nymphs and adults of Clastoptera sp. are recorded for the first time on coffee plants (Coffea arabica L.) in Brazil. Specimens adults were deposited in the insects collection of Department of Entomology, Plant Pathology and Zoology, ESALQ/USP, in Piracicaba, Sao Paulo, Brazil.